(3GdRjGOGJ GdehLhOGJ ef cJGH GdoeYLe aj oeTJHg CSeGA GdeMOKjfs - (3GdMGaX CHh GdaVd YHjO Gddg Hf YHO Gddg Hf CMeO Hf eMeO Hf jhSa GdgQhjs ((3CHhHcQ Hf Ydj Hf ESeGYjd GdHgfSj GdCfUGQj GdTGaYj s)
(3ChdgG (B:s
(3ESeGYjd Hf eSde CQHYI , jQhf Yf GdJGHYjf EdN s
(3BNQgG (B:s
(3BNQ eG hLO ef GdRjGOGJ aj cJGH GdoeYLe s
(3Vef eLehY , JQJjHgG (B: (3ef U (B153 - (3U(B157s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B80 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(624) s
Keywords: (3GdJGQjNs